Implementasi Model Pembelajaran Literasi Sejarah Berbasis Discovery Learning - Lionar, Uun; Mulyana, Agus; Winarti, Murdiyah; Sapriya, Sapriya; Afriani, Rini; Yefterson, Ridho Bayu (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
The main objective of this research is to analyze the implementation of a history literacy learning model based on discovery learning in Social Studies Education for grade X at Senior High School. A mixed methods intervention design was used in this study. The subjects of the research were teachers and students from Pertiwi Senior High School in Padang City, West Sumatra Province. Data collection was conducted through direct observation of classroom activities, interviews with 29 students and 1 teacher regarding their experiences in the learning process, and tests in the form of pretests and posttests to assess learning outcomes before and after the implementation of the learning model. The results of this study indicate that quantitatively, the use of the history literacy learning model based on discovery learning has a positive impact on students' learning outcomes, as evidenced by the differences in learning results before and after the model was implemented. Qualitatively, this model has encouraged students to engage directly in exploring historical information, providing them with experiences while training them to think critically and analytically about various historical narratives. This research implies the importance of applying the history literacy learning model based on discovery learning in Social Studies Education at senior high schools within the framework of the Merdeka Curriculum. Teachers can use this model to facilitate students in developing their understanding of history and training various skills that are needed.